Revitalisasi Plang Sampah sebagai Langkah Efektif Pengelolaan Lingkungan Kelurahan Tembokrejo Kota Pasuruan - Andjani Sulistyaningrum Kinasih; Amirotul Muniroh; Akhmad Rafiqin; Anindia Dwitri; Lingga Wisma Angga Saputro (Universitas Negeri Surabaya, 2025)
The problem that occurs in Tembokrejo Village is the lack of public awareness in disposing of waste which is still done carelessly. Anticipation verbally for the PkM (Community Service) team to increase public awareness about waste disposal, especially through a program to install signs prohibiting littering. The initial step is to survey the location of the sign installation. Then, sanding and painting are carried out as well as renewal of signs from the Public Works and Spatial Planning Agency (DPUPR) of Pasuruan City and the Water Resources and Drainage Agency (SDAD). Then, the process of installing signs by the PkM team was assisted by the SDAD Agency and DPUPR of Pasuruan City and produced 4 signs. The PkM team used interviews as an evaluation of the effectiveness of signs for public awareness of cleanliness. KKN students hope that the presence of these signs can attract the attention of the surrounding community to comply with these regulations so that a clean and healthy environment is created. Keywords: Placing signs, Tembokrejo Village